2010
DOI: 10.1071/fp09202
|View full text |Cite
|
Sign up to set email alerts
|

The response of barley to salinity stress differs between hydroponic and soil systems

Abstract: Many studies on salinity stress assume that responses in hydroponics mimic those in soil. However, interactions between the soil solution and the soil matrix can affect responses to salinity stress. This study compared responses to salinity in hydroponics and soil, using two varieties of barley (Hordeum vulgare L.). The responses to salinity caused by high concentrations of Na+ and Cl– were compared to assess any consistent differences between hydroponics and soil associated with a cation and an anion that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 44 publications
3
93
0
Order By: Relevance
“…The other is that soil is a very different ionic medium from solution culture. A clay soil can influence Na + and Clavailability and can result in different growth responses (Tavakkoli et al 2010). There is, therefore, the need to confirm the usefulness of results found in controlled environments in the typical soils and ambient conditions that occur in grain production fields.…”
Section: Introductionmentioning
confidence: 99%
“…The other is that soil is a very different ionic medium from solution culture. A clay soil can influence Na + and Clavailability and can result in different growth responses (Tavakkoli et al 2010). There is, therefore, the need to confirm the usefulness of results found in controlled environments in the typical soils and ambient conditions that occur in grain production fields.…”
Section: Introductionmentioning
confidence: 99%
“…This has been primarily due to the fact that several studies have shown a lack of correlation between the ability to exclude Na and the overall tolerance of a genotype (Genc et al 2007). It is evident that a combination of different mechanisms (exclusion, extrusion, compartmentation and cellular tolerance) are responsible, and not solely ion exclusion or ion extrusion (Tavakkoli et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…More recently (Almansouri et al 1999), a study has shown that expression of this two-phase response, initially suggested (Munns et al 1995), as a simplistic explanation for genetic differences in salt tolerance of wheat cultivars, was even influenced by how the salt stress was imposed; whether sudden or progressive. More recently, it has been observed (Tavakkoli et al 2010) that the expression of differences in these two components amongst barley cultivars is also influenced by what kind of system was used, whether a hydroponic system or a soil system. The concept of exclusion ability of genotypes being the primary determinant of salt tolerance has itself come in for re-evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in growth with increased salinity levels might be due to limited supply of metabolites to young growing tissue as a result of either metabolic disturbance or low water uptake along with toxic effects of sodium Adjel et al (2013). High external concentrations of Cl -had similar adverse effects as high concentrations of Na + , suggesting that Cl -toxicity may reduce growth Tavakkoli et al (2010). Fundamental differences in salinity responses appeared between soil and solution culture, and the importance of the different mechanisms of damage varies according to the severity and duration of the salt stress Ehsan et al (2010).…”
Section: Discussionmentioning
confidence: 99%